Defining ‘nutraceuticals’: neither nutritious nor pharmaceutical - Aronson, Jeffrey K. (Br J Clin Pharmacol, 2016)
There are widespread inconsistencies and contradictions in the many published definitions of ‘nutraceuticals’ and ‘functional foods’, demonstrating wholesale uncertainty about what they actually are. Furthermore, in a 2014 lecture, the inventor of the term ‘nutraceutical’, confessing that nutraceuticals do not work, said that ‘the quest to demonstrate whether … long‐term supplementation [with nutraceuticals] can prevent serious diseases … has come to an end’. Definitions of ‘nutraceuticals’ and related terms, still widely used, should therefore be explored systematically. There are no internationally agreed definitions of ‘nutraceuticals’ and ‘functional foods’, or of similar terms, such as ‘health foods’, or of terms related to herbal products, which are sometimes referred to as ‘nutraceuticals’, compounding the confusion. ‘Nutraceuticals’ and ‘functional foods’ are vague, nondiscriminatory, unhelpful terms; the evidence suggests that they should be abandoned in favour of more precise terms. The term ‘dietary supplement’ is widely used to designate formulations that are also called ‘nutraceuticals’ but it would be better restricted to individual compounds used to treat or prevent deficiencies. ‘Fortified foods’, sometimes called ‘designer foods’, are foods to which compounds of proven therapeutic or preventive efficacy (e.g. folic acid) have been added. Other terms, such as ‘food’, ‘foodstuffs’, ‘eat’, ‘drink’, and ‘nutrition’, are well defined, as are ‘medicinal products’ and ‘pharmaceutical formulations’. Dietary regimens, such as Mediterranean or nitrate‐rich diets or vegetarianism, can affect health. A dietary regimen of this kind can be defined as a programme of food, of a defined kind and/or quantity, prescribed or adopted for the restoration or preservation of health.